Analisis Faktor yang Mempengaruhi Kinerja Pegawai - Nugraha Pratama (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to determine and analyze the effect of work discipline on the performance of employees of PT. BPJS Employment at Binjai Branch. To find out and analyze the influence of communication on the performance of employees of PT. BPJS Ketenagakerjaan at Binjai Branch. To find out and analyze the effect of work discipline and communication on the performance of employees of PT. BPJS Employment at Binjai Branch. From the above discussion, it can be concluded in this study are as follows: From the results of this study, the value of the discipline's significance based on the t test was obtained at 0.000 (Sig 0.000 <?0.05). thus Ho is rejected and H1 is accepted. The conclusion: there is a significant effect of discipline on performance. From the results of this study, it was found that the communication significance value based on the t test was obtained at 0.000 (Sig 0.002 <?0.05). thus Ho is rejected and H1 is accepted.